2019
DOI: 10.1111/codi.14734
|View full text |Cite
|
Sign up to set email alerts
|

Colorectal cancer patients under the age of 50 experience delays in primary care leading to emergency diagnoses: a population‐based study

Abstract: Aim The incidence of colorectal cancer in the under 50s is increasing. In this national population‐based study we aim to show that missed opportunities for diagnosis in primary care are leading to referral delays and emergency diagnoses in young patients. Method We compared the interval before diagnosis, presenting symptom(s) and the odds ratio (OR) of an emergency diagnosis for those under the age of 50 with older patients sourced from the cancer registry with linkage to a national database of primary‐care re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
32
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(33 citation statements)
references
References 22 publications
1
32
0
Order By: Relevance
“…As cancer is more common in the elderly, doctors are more inclined to suspect cancer in older patients [ 1 ] and younger patients are more likely than older people to have consulted with a doctor three or more time before referral [ 2 , 3 ]. Even when referred, younger patients may be referred through a less urgent route compared to older ones [ 4 ]. A delay in diagnosis may result in cancer progressing to a less curable stage.…”
Section: Introductionmentioning
confidence: 99%
“…As cancer is more common in the elderly, doctors are more inclined to suspect cancer in older patients [ 1 ] and younger patients are more likely than older people to have consulted with a doctor three or more time before referral [ 2 , 3 ]. Even when referred, younger patients may be referred through a less urgent route compared to older ones [ 4 ]. A delay in diagnosis may result in cancer progressing to a less curable stage.…”
Section: Introductionmentioning
confidence: 99%
“…Bowel symptoms in younger patients may be attributed by clinicians to common benign colorectal disease, such as rectal bleeding from haemorrhoids or abdominal pain from irritable bowel syndrome [9][10][11]. Unfortunately, younger patients who report non-specific symptoms but who have an underlying CRC may require multiple visits before referral for investigation, resulting in longer time to diagnosis [12][13][14][15]. A survey of EOCRC patients in the UK reported that 43% of patients required three or more visits to their primary care physician (PCP) before referral to secondary care for further investigation, and that 65% were initially given an incorrect diagnosis [11].…”
Section: Introductionmentioning
confidence: 99%
“…Patients themselves may not suspect their bowel symptoms may be due to cancer: in the same survey, 75% of patients did not suspect their symptoms were due to CRC, and 30% delayed seeing their PCP for up to 3 months [11]. The interval from referral to diagnosis in younger patients is significantly longer in younger patients in national UK data, probably due to an absence of criteria indicating urgent referral for suspected cancer [12]. National cohort data also report that EOCRC more commonly presents as an emergency, at a more advanced stage of diagnosis [12,14,16,17], although younger patients tend to have better survival than older patients [18,19].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Instead, these patients were more likely to have presented to their primary care provider, in the year before diagnosis, with nonspecific symptoms. 24 Individuals having ABO blood group B were in peak regarding developing colorectal carcinoma according to this study. 63% colorectal carcinomas were presented with tumour size ≤ 4 cm in this study.…”
Section: Discussionmentioning
confidence: 54%